Towards a Practical Development of Light‐Driven Acceptorless Alkane Dehydrogenation. (14th May 2014) - Chowdhury, Abhishek Dutta; Weding, Nico; Julis, Jennifer; Franke, Robert; Jackstell, Ralf; Beller, Matthias
Abstract: The efficient catalytic dehydrogenation of alkanes to olefins is one of the most investigated reactions in organic synthesis. In the coming years, an increased supply of shorter‐chain alkanes from natural and shale gas will offer new opportunities for inexpensive carbon feedstock through such dehydrogenation processes. Existing methods for alkane dehydrogenation using heterogeneous catalysts require harsh reaction conditions and have a lack of selectivity, whereas homogeneous catalysis methods result in significant waste generation. A strong need exists for atom‐efficient alkane dehydrogenations on a useful scale. Herein, we have developed improved acceptorless catalytic systems under optimal light transmittance conditions using trans ‐[Rh(PMe3 )2 (CO)Cl] as the catalyst with different additives. Unprecedented catalyst turnover numbers are obtained for the dehydrogenation of cyclic and linear (from C4 ) alkanes and liquid organic hydrogen carriers. These reactions proceed with unique conversion, thereby providing a basis for practical alkane dehydrogenations. Abstract : „Grün" dank blauem Licht : Die effiziente lichtinduzierte atomökonomische Dehydrierung verschiedener linearer und cyclischer Alkane (einschließlich Erdgasbestandteilen und flüssigen organischen Wasserstoffträgern) gelang mit trans ‐[Rh(PMe3 )2 (CO)Cl] als Katalysator in Gegenwart eines stickstoffhaltigen Additivs. Die Methode bietet eine saubere Alternative zum direkten Einsatz von Alkanen als Olefinquelle.